False Consciousness: The Cultural Identity Construction of Cele And Batik Within Moluccan Scholars in Ambon - Elka Anakotta; Flavius Floris Andries (Al-Albab, 2021)
Identity is a social construction. The Moluccan people are evident of this structure, especially regarding the policy of the obligation to wear cele (Moluccan traditional garment). This has become a process of identity construction involving culture and ethnicity for Moluccans. This paper discusses how Moluccan scholars who studied in Java understand their position wearing cele in the local context in Maluku. In addition, this paper also discusses the scholars’ views on how the process of identity negotiation between localism and nationalism is represented through cele and batik. Information for this study was gathered using a qualitative method with a cultural studies approach. The data were collected using several techniques including interviews, observation, and literature studies to answer research questions and problems. This paper shows that in response to the Moluccan government policy which requires the people to wear cele once a week, most scholars prefer to wear batik instead. One justification is related to cultural and religious aspects, noting cele is more familiar and originates from within the Christian community, while the Islamic community does not recognize cele in their culture. They consider that such policy leads to the construction of cultural identity based on false consciousness.